2023
DOI: 10.1039/d3ma00089c
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired green-synthesized silver nanoparticles: in vitro physicochemical, antibacterial, biofilm inhibitory, genotoxicity, antidiabetic, antioxidant, and anticoagulant performance

Hamed Barabadi,
Omid Hosseini,
Kamyar Jounaki
et al.

Abstract: Green-synthesized nanobiomaterials, for instance silver nanoparticles (AgNPs), can be engineered as smart nanomedicine platforms for diagnostic and therapeutic purposes of various disorders including infectious diseases and cancer. In the present...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 59 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…For example, the Anticoagulant activity of AgNPs mycogenically synthesized using Bacillus safensis LAU 13 cell-free extract was examined visually by Lateef et al. [41] According to the research depicted in Figures 4 a and b, it was discovered that AgNPs had strong Anticoagulant properties and inhibited the Exhibited substantial anticoagulant action at 1 mg/mL as opposed to saline the -ve control [66] formation of blood clots. It was conclusively proven that mycogenic AgNPs fiercely compete with the + ve control (EDTA), as seen in Figure 4a2, and the microscopic view also revealed evenly distributed red blood cells (Figure 4c2).…”
Section: Antithrombolytic Anticoagulant and Antiplatelet Activities O...mentioning
confidence: 99%
“…For example, the Anticoagulant activity of AgNPs mycogenically synthesized using Bacillus safensis LAU 13 cell-free extract was examined visually by Lateef et al. [41] According to the research depicted in Figures 4 a and b, it was discovered that AgNPs had strong Anticoagulant properties and inhibited the Exhibited substantial anticoagulant action at 1 mg/mL as opposed to saline the -ve control [66] formation of blood clots. It was conclusively proven that mycogenic AgNPs fiercely compete with the + ve control (EDTA), as seen in Figure 4a2, and the microscopic view also revealed evenly distributed red blood cells (Figure 4c2).…”
Section: Antithrombolytic Anticoagulant and Antiplatelet Activities O...mentioning
confidence: 99%
“…[20] It was also observed that E. coli (ATCC 11229) and Staphylococcus epidermidis (ATCC 12228) were both significantly inhibited by plant-mediated synthetic AgNPs. [20] Various other uses of AgNPs are also possible. For instance, AgNPs synthesized with certain chemicals (acetic acid, ascorbic acid) and a solution of chitosan biopolymer as a stabilizing agent are in the treatment of dental caries.…”
Section: Introductionmentioning
confidence: 97%
“…(Table 1). [20] It was also observed that E. coli (ATCC 11229) and Staphylococcus epidermidis (ATCC 12228) were both significantly inhibited by plant‐mediated synthetic AgNPs [20] . Various other uses of AgNPs are also possible.…”
Section: Introductionmentioning
confidence: 99%
“…Nanobiotechnology is a rapidly expanding field in biological sciences that has various applications in the health sector, particularly for the production of bioactive nanomaterials such as nanoparticles (NPs) and nanoconjugates for controlling several diseases. Green nanotechnology-based NPs and nanoconjugates have attracted huge interest because of their extensive biomedical applications [1][2][3]. NPs have shown promising results as alternative drugs for human diseases, including cancer, diabetes, wound healing and infectious diseases [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Biosynthesized NPs have several advantages, including less toxicity and high stability [11,15,16]. Moreover, the biosynthesized NPs show a wide range of biomedical applications such as antioxidant, antimicrobial, anti-inflammation and anti-cancer agents as well as promising carriers for various drug delivery systems [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%